Preparing for CompTIA A+ - Exam 220-901 (2015 objectives) : understanding the knowledge sets required to pass the CompTIA A+ 220-901 exam - Long, Mark (O'Reilly, 2016)
"The CompTIA A+ certification is recognized by employers world-wide as a demonstration of computer technician competency. Two CompTIA exams must be passed before a person can obtain the A+ certification. In this video, CompTIA pro Mark Long uses hands-on demonstrations, photos, and animations to review the content covered in the first exam: 220-901. A key benefit of this video is instruction on how to obtain a copy of CompTIA's published 2015 objectives. Knowing the objectives helps you identify your knowledge weaknesses and allows you to focus on what you need to know to pass the exam. The course is targeted at beginning level computer technicians eager to land their first real IT jobs as well as existing A+ certification holders who need to re-certify."--Resource description page.